Exploring the Impact of Customer Data Security on Consumer Trust in Gojek's Digital Services - Ferdyan Putri, Zahra Qanitah; Efawati, Yen (Asosiasi Ahli Administrasi Indonesia, 2025)
This study aims to explore the effect of customer data security on consumer confidence in using Gojek digital services. The main focus of the research is to analyze the impact of customer data security on the Gojek platform regarding consumer perceptions and levels of trust in the service. The research method employed is descriptive with a quantitative approach, involving a population of students at Politeknik Negeri Bandung, Indonesia, for the period 2020–2023. Data were collected using questionnaires and analyzed through simple regression analysis. Results showed that approximately 38.3% of consumer confidence in Gojek services can be explained by customer data security factors. Simple regression analysis reveals significant variable coefficients, highlighting the important role of data security in shaping consumer trust. Although the impact is relatively modest, customer data security remains a crucial determinant in enhancing consumer trust in Gojek's digital services. The remaining 61.7% is influenced by other factors not examined in this study, such as service quality, user experience, and brand reputation. This research contributes to a deeper understanding of the relationship between data security and consumer trust in the context of digital services. It also offers practical insights for digital service providers like Gojek to strengthen consumer trust by improving data protection measures. Future research is recommended to explore additional factors influencing consumer trust and to conduct comparative studies across different digital platforms.